Design Studio. Volume 1, 2021 Everything needs to change : architecture and the climate emergency - Pelsmakers, Sofie; Newman, Nick (London : RIBA Publishing, 2021)
Want to keep up with emerging design thinking and issues worldwide? Design Studio is a new thematic series that distils the most topical work and ideas from schools and practices globally. The first volume launches with a statement: Everything Needs to Change. Exploring architecture and the climate emergency, editors Sofie Pelsmakers (author of Environmental Design Sourcebook) and Nick Newman (climate activist and Director at Studio Bark), are channelling the message of Greta Thunberg to inspire, enthuse and inform the next generation of architects. Featuring articles, building profiles and case studies from a range of leading voices, it explores solutions to climatic, environmental and social challenges. It urges readers to radically rethink what it means to be an architect in an era of climate crisis, and what the role of the architect is or can be. Discover how using local materials, working with nature, radical design processes, transformative learning and activism can help us find hope in the burning world. Together, we can force change for a more sustainable and equitable tomorrow. This first volume is produced in four unique fluorescent colours - green, red, yellow and purple - to be your own poster for change.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable architecture; Sustainable architecture -- Case studies; Architecture and climate